PENGARUH PERBEDAAN PROSES PENYEDIAAN SERAT DENGAN CARA MEKANIS LIMBAH TANDAN KOSONG SAWIT TERHADAP PAPAN SERAT - Roza, Irwan (Sainstek, 2009)
The research about the influence of the difference fiber provider process from the empty stem palm sludge to the fiber board has been done in the laboratory of forestry faculty on the Muhamadyah university, West Sumatera, and the laboratory of agriculture output technology in the agriculture faculty of Andalas University, also in the civil enginering laboratorium of Padang polytechnic. The research done since March until June 2008. the research’s purpose is to understand the influence of the difference fiber provider from the empty stem palm sludge to create the fiber board where the result arranged from the differ components (mass material as same as the treatment) to the fiber board and to evaluate the characteristic from the fiber board that has been created. To understand the influence of the difference fiber provider from the empty stem palm sludge to create the fiber board to distinguish the mass material among others: 100% mass material, 94% mass material, 62% mass material, and 32% mass material. The research use the complex random design with 4 treatment ang 5 times repeatation, then continued by using duncan’s new multiple range test (DNMRT) at the 5% significant extent to test the water content and the fiber board density and continued at the 15% significant extent. The result shows that the fiber provider with 94% has qualified the SNI 1996 except for the absorbtion capability and the development of thick. Althougth the fiber provider with the mass material of 62% and 32% contribute more value but does not effective to be applied in the wood panel industry. The fiber characteristic from the palm’s empty stem with the mass material 94% as follows: 9.59% water content, 4.25% extractive substances, 23.14% lignin content, 65.09% degree holosellulosa, 46.49% degree sellulosa. Physical characteristic of fiberboard with a mass of 94% as follows: 8.70% water content, 0.7477 g/cm3 density, 73.40% the absorption capability of water, and  50.92% the value of the development of thick. While for the mechanical characteristic of fibreboard produced as follows: 80.8720 kg/cm2 broken persistence, 49.1767 kg/cm2 persistence press and 6.4863 kg/cm2 internal fortitude sticking. Key Words:     Papan serat, selulosa, lignin, serat